PERAN INTERNATIONAL COMMITTEE OF THE RED CROSS (ICRC) DALAM MEMBENTU KORBAN PERANG PADA KONFLIK NAGORNO-KARABAKH TAHUN 2020 - Roihan Alfaini; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This journal research aims to determine the relationship between the role of international organizations, in the issue of human security in conflict situations. Where in this case, the Author takes a case study of the role of the International Committee of the Red Cross (ICRC) in helping to provide assistance to victims of war in the Nagorno-Karabakh conflict situation in 2020. The role of the ICRC itself is carried out with the aim of providing protection to parties who became victims of the threats posed by the war situation that occurred. The type of research used in this research is qualitative using descriptive research methods. The data used is secondary data sourced from journals, books, reports, to websites related to the thesis research theme. That is about the ICRC's role in helping war victims in the Nagorno-Karabakh conflict that occurred in 2020. The results of this study indicate that the ICRC has an important role in helping war victims in the Nagorno-Karabakh conflict in 2020. Where the role of the ICRC itself can be divided into three different roles. Such as an instrument, forum, and independent actor. As an instrument, the ICRC has a role to play as a tool for its members to achieve certain goals; which in this case, is to help war victims in the 2020 Nagorno-Karabakh conflict. As an forum, ICRC has the role of being a forum in facilitating communication between the actors involved. Especially communication concerning the interests of protecting the victims of war. Meanwhile as an independent actor, the ICRC has carried it out without the influence of outside interests. With the principle of neutrality, the ICRC can carry out its program in the Nagorno-Karabakh conflict without any interest in taking sides or supporting certain parties involved in the conflict. Keywords: Role, ICRC, Human Security, Victims of War, Conflict.